THE ASSOCIATION OF IMMUNE RESPONSE TO XENOAND ENDOBIOTIKS AND THEIRS BIOTRANSFORMATION ENZYME GENE POLYMORPHISM WITH CONGENITAL MALFORMATIONS OF THE FETUS - K. S. Krasilnikova (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
The correlation between immune response to benzo(a)pyrene and progesterone in combination with detoxification enzyme gene polymorphism (CYPIA2*1F and GSTTI) and the occurrence of congenital malformations of the fetus was revealed. It is shown that at high ratio of IgA-antibodies to benzo(a)pyrene and to progesterone in conjunction with the mutant allele of the gene CYPIA2*1F and the deletion genotype of the gene GSTTI chance of the reproductive pathology developing increases to 41 times.